Appraisal Values Recognized in ELT-SOLO Readers’ Series - Agnes Widyaningrum (Universitas Stikubank (UNISBANK) Semarang, 2015)
The role of English nowadays reaches many fields including early education at school. The number of Indonesian students who are able to speak English fluently is increasing. Moreover, in many big cities we can find many Indonesian families who live in Indonesia but their children talk in English instead of Bahasa Indonesia. Is it a thread or not? If we see from the students’ ability in using English this picture represents the result of Teaching English in Indonesia since early childhood.The Indonesian students are not likely to read books though they know that by reading they will get more knowledge and information. The gadget attacks them because they are likely to read things in their gadget then from the books. This is not a very good situation if the number of students who do not want to read increased. The Indonesian reading habit is lower than the students from our neighboring countries. This reading habit is one of indicators that can measure the future generation of Indonesian students. The teachers should work hand in hand with the family to create reading habit because by reading they can improve their vocabulary. By improving the vocabulary they can speak and write English better. The student’s vocabulary will improve if they have good reading habit because if they do not want to read therefore their vocabulary remains the same. Learning English from the vocabulary is one kind of learning strategies done by the teachers who teach basic level. The more they read the English books the more vocabulary they will get.This documentary study is analyzed in qualitative nature by giving detailed explanation for data. The step to collect the data is reading the books and the steps to analyze the data are identification, classification and interpretation. The result shows that there are appraisal values recognized in ELT-SoloReaders’ series with the purpose to teach young readers to learn how to share their ideas and appreciate others’ ideas in English correctly. Keywords:reading habit, vocabulary, learning strategy, appraisal values